China-Pakistan Economic Corridor (CPEC): A Paradigm Shift in Power Politics - Azmat Ullah، Muhammad Anwar (JSSH, 2024)
Pakistan and China has long history of deep rooted and time-tested friendship. The changes of power in both states do not affect their relations. Since the beginning of CPEC which is a mega project of China’s One Belt One Road (OBOR) strategy and is a great step in cementing Pak-China nexus, is also seen and surmised by the world powers as a paradigm shift in the power politics that might lead towards new polarizations. World powers are showing varied attitudes towards CPEC and are keenly observing new developments.